Anti-lock Braking System Control Based on Fuzzy Logic - kocak, sinan; Shamshiden, Nurlybek (Bánki Közlemények, 2021)
Safety driving systems of the vehicles such as Anti-lock Braking System (ABS) assists drivers to control automotive to safe from road accidents. It is possible to reduce these accidents with proper calculations. The traditional ABS method used is reliable, but it can be developed using different techniques. In this article, fuzzy logic-controlled ABS is implemented to improve braking performance and directional stability by comparing two different defuzzification techniques. In the Fuzzy Logic Toolbox of the MATLAB package program, remarkable results have been obtained by using Centroid (COG) and Middle of Maxima (MoM) defuzzification methods.